The Importance of Transversal Competencies in University Education: Self-efficacy for Entrepreneurial Leadership in Health Sciences: The Importance of Transversal Competencies in University Education: Self-efficacy for Entrepreneurial Leadership in Health Sciences - San Martín González, Paula; Hortiguela Alcalá, David; Amatria Jiménez, Mario; Arroyo del Bosque, Rubén (Revista Complutense de Educación, 2026)
INTRODUCTION: The mastery of transversal competencies in university education has become increasingly relevant within the framework of the European Higher Education Area (EHEA). In the field of Health Sciences, attention has been predominantly directed towards the development of specific competencies, while transversal competencies have been underestimated, despite their critical importance in the comprehensive training of professionals. This study aims to analyze self-efficacy in entrepreneurial leadership among students of different degrees in Health Sciences, specifically in the degrees of Nursing, Physiotherapy and Physical Activity and Sport Sciences (CAFYD). METHOD: A quantitative study was conducted with a sample of 101 students enrolled in different Spanish universities during the academic year 2022-2023, whose ages ranged from 19 to 31 years (22.57 ± 1.80). For the measurement of self-efficacy, the Spanish adaptation of the CESE scale (Moriano et al., 2012) was used. RESULTS: The results indicate that students of the Bachelor's Degree in Physical Activity and Sport Sciences report a significantly higher perception of self-efficacy in entrepreneurial leadership compared to their peers in Physiotherapy and Nursing. DISCUSSION: These findings highlight the urgent need to incorporate leadership training into the curricula of Physical Activity and Sport Science undergraduate programs.
Keywords: Leadership; Health; Innovation; University